2017
DOI: 10.1080/00952990.2016.1278006
|View full text |Cite
|
Sign up to set email alerts
|

The ALERRT® instrument: a quantitative measure of the effort required to compromise prescription opioid abuse-deterrent tablets

Abstract: Background: US FDA guidance recommends measuring the degree of effort needed to manipulate abuse-deterrent (AD) opioids. The ALERRT ® instrument (PinneyAssociates; Bethesda, MD) uses visual analog scales to assess the labor, effort, and resources necessary to physically compromise AD product candidates in standardized settings. Objective: Use the ALERRT ® instrument for testing morphine abuse-deterrent, extended-release, injection-molded tablets (ADER-IMT) 60 and 100 mg and the comparators immediate-release (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Syringeability and injectability studies that involved exposing untreated and heat‐pretreated morphine‐ADER‐IMT tablets to a variety of solvents produced a viscous mass with low syringeability (syringe content <10% of starting content), compared with 30% to 60% of non‐ADF ER morphine that was syringeable in volumes suitable for injection . In addition, an evaluation of the degree of effort required to manipulate morphine formulations with different household tools reported that morphine‐ADER‐IMT was extremely difficult to manipulate and required considerably more effort and time to manipulate than non‐ADFs of IR and ER morphine, which may reduce the attractiveness of morphine‐ADER‐IMT for misuse and abuse since it cannot be readily prepared for injection . None of the extraction tools enabled complete or substantial powdering of morphine‐ADER‐IMT, whereas using the same tools for manipulation resulted in complete or substantial powdering for 97.2% of IR morphine sulfate tablets and 77.1% of ER morphine sulfate tablets …”
Section: Abuse‐deterrent Er/la Opioid Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Syringeability and injectability studies that involved exposing untreated and heat‐pretreated morphine‐ADER‐IMT tablets to a variety of solvents produced a viscous mass with low syringeability (syringe content <10% of starting content), compared with 30% to 60% of non‐ADF ER morphine that was syringeable in volumes suitable for injection . In addition, an evaluation of the degree of effort required to manipulate morphine formulations with different household tools reported that morphine‐ADER‐IMT was extremely difficult to manipulate and required considerably more effort and time to manipulate than non‐ADFs of IR and ER morphine, which may reduce the attractiveness of morphine‐ADER‐IMT for misuse and abuse since it cannot be readily prepared for injection . None of the extraction tools enabled complete or substantial powdering of morphine‐ADER‐IMT, whereas using the same tools for manipulation resulted in complete or substantial powdering for 97.2% of IR morphine sulfate tablets and 77.1% of ER morphine sulfate tablets …”
Section: Abuse‐deterrent Er/la Opioid Formulationsmentioning
confidence: 99%
“…In addition, an evaluation of the degree of effort required to manipulate morphine formulations with different household tools reported that morphine‐ADER‐IMT was extremely difficult to manipulate and required considerably more effort and time to manipulate than non‐ADFs of IR and ER morphine, which may reduce the attractiveness of morphine‐ADER‐IMT for misuse and abuse since it cannot be readily prepared for injection . None of the extraction tools enabled complete or substantial powdering of morphine‐ADER‐IMT, whereas using the same tools for manipulation resulted in complete or substantial powdering for 97.2% of IR morphine sulfate tablets and 77.1% of ER morphine sulfate tablets …”
Section: Abuse‐deterrent Er/la Opioid Formulationsmentioning
confidence: 99%
“…ADFs are specifically designed to deter the use of opioids via unintended routes of administration, including intranasal and intravenous routes, which have been reported to double the risk for life‐threatening events and death . During this period of technological progress, new methods to assess potential abuse‐deterrent (AD) characteristics of ADFs have also been developed . Although guidance documents have been published regarding the development and labeling of new ADFs, until 2016, none of these initiatives addressed the requirements for generic ADFs .…”
Section: Introductionmentioning
confidence: 99%
“…3 During this period of technological progress, new methods to assess potential abuse-deterrent (AD) characteristics of ADFs have also been developed. 4 Although guidance documents have been published regarding the development and labeling of new ADFs, until 2016, none of these initiatives addressed the requirements for generic ADFs. 5 In March 2016, the U.S. Food and Drug Administration (FDA) released a draft guidance titled "General Principles for Evaluating the Abuse Deterrence of Generic Solid Oral Opioid Drug Products" (referred to as the opioid generic drug [OGD] guidance in this commentary) to address generic ADFs, which was subsequently finalized in November 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Morphine abuse-deterrent, extended-release injection-molded tablets (morphine-ADER-IMT) are a unique AD, ER morphine product candidate incorporating a proprietary technology (Guardian, Egalet Corporation, Wayne, PA, USA) that is a polymer matrix tablet with a novel manufacturing process, plastic injection molding. This technology results in ER tablets with physical and chemical features that resist both common and more rigorous methods of manipulation, which limits particle size reduction and extraction of the active pharmaceutical ingredient (API) [ 13 ]. Using a recently developed instrument, Assessing Labor, Effort and Resources Required for Tampering (ALERRT; Pinney Associates, Bethesda, MD, USA), morphine-ADER-IMT was shown to be extremely difficult to manipulate [ 14 ].…”
Section: Introductionmentioning
confidence: 99%